2018
DOI: 10.1016/j.cell.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Regulates Phase Separation of PGL Granules to Modulate Their Autophagic Degradation

Abstract: The assembly of phase-separated structures is thought to play an important role in development and disease, but little is known about the regulation and function of phase separation under physiological conditions. We showed that during C. elegans embryogenesis, PGL granules assemble via liquid-liquid phase separation (LLPS), and their size and biophysical properties determine their susceptibility to autophagic degradation. The receptor SEPA-1 promotes LLPS of PGL-1/-3, while the scaffold protein EPG-2 controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
161
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(165 citation statements)
references
References 32 publications
3
161
0
1
Order By: Relevance
“…We suggest that germ granules are not crucial for RNAi per se, but rather are important for small RNA homeostasis, with consequences that can persist for multiple generations. Previous studies have shown that the stability of the germ granules is affected by environmental changes (for instance temperature 55,56 ), and also that temperature shifts trigger changes in heritable small RNAs 3,57 . Because germ granules impact small RNA biogenesis, the granules could be important mediators in the translation of environmental changes to small RNA-mediated transgenerational memory.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that germ granules are not crucial for RNAi per se, but rather are important for small RNA homeostasis, with consequences that can persist for multiple generations. Previous studies have shown that the stability of the germ granules is affected by environmental changes (for instance temperature 55,56 ), and also that temperature shifts trigger changes in heritable small RNAs 3,57 . Because germ granules impact small RNA biogenesis, the granules could be important mediators in the translation of environmental changes to small RNA-mediated transgenerational memory.…”
Section: Discussionmentioning
confidence: 99%
“…protein with at least two multimerization domains) 1, 33 . Because PGLs are key assembly proteins for P-granules and can form granules on their own 6, 11, 24, 25 , we reasoned that PGLs use multiple self-interactions to drive granule assembly. We previously identified one dimerization domain (DD) centrally in PGL 27 , but DD missense mutations grossly affected protein stability.…”
Section: Resultsmentioning
confidence: 99%
“…Our work highlights the idea that interactions between structured regions are a driving force in vivo for assembly of liquid droplet granules as well as their biological function (see below). Recombinant PGL proteins make liquid droplets on their own in vitro 6, 11, 24 , suggesting that PGLs possess regions responsible for low affinity contacts in the full-length protein. We suggest that PGL uses both dimerization domains as well as additional low affinity contacts to facilitate liquid droplet formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations